Post-silking Phosphorus Recycling and Carbon Partitioning in Maize Under Low to High Phosphorus Inputs and Their Effects on Grain Yield - Wang, Chao; Ning, Peng (Frontiers in Plant Science, 2019)
Phosphorus (P) recycling and carbon partitioning are crucial determinants of P-use efficiency and grain yield in maize (Zea mays), while a full understanding of how differences in P availability/plant P status affect these two processes underlying yield formation remains elusive. Field experiments were conducted for 3 years to investigate the maize growth, P remobilization, and carbohydrate accumulation in leaves and developing ears of plants receiving low to high P inputs. In plots that 75 kg P2O5 ha-1 and above was applied (corresponding to 7.5 mg kg-1 and higher Olsen-P concentration in 0–20 cm soil layer), no additional response occurred in leaf area, ear growth, and grain yield. Despite the higher P uptake with P fertilization above this threshold, the lack of additional plant growth and yield resulted in decreased P-use efficiency. Regardless of P application rates, P remobilization to the ear during the first half of the grain filling phase preferentially came from the stem (50–76%) rather than from leaves (30–44%), and with a greater proportion in the inorganic P (Pi) form over organic P fractions. Leaf photosynthesis was maintained under P-limiting conditions due to the greater P investment in organic P pools than Pi. More and larger starch granules were found in the bundle sheath cells at silking or 21 days after silking (DAS) than under P-sufficient conditions. The amount of total carbohydrate production and export was lower in the P-deficient plants than the high-P plants, corresponding to decreased leaf size and lifespan. Nonetheless, similar or significantly greater starch levels were observed in both cob and kernels at silking and 21 DAS, implying there was an adequate carbohydrate supply to the developing ears under the diminished kernel sink of the P starvation. In addition, there was a strong correlation between the accumulation rates of carbon and remobilized P in the developing kernels, as well as between carbon and total P. Overall, the results indicated that diminished sink size and lower capacity of carbon deposition may limit yield formation in P-deficient maize, which in turn imposes a feedback regulation on reducing carbon and P remobilization from source leaves. An integrated framework considering post-silking P recycling and carbon partitioning in maize and their effects on grain yield has been proposed.